169 Endothelial Insulin Sensitisation Enhances Vascular Repair and Aortic Vasomotor Function in Systemic Insulin Resistance. (31st May 2014) - Sengupta, Anshuman; Viswambharan, Hema; Yuldasheva, Nadira; Ben Mercer, Noman Ali; Walker, Andrew; Galloway, Stacey; Aziz, Amir; Gage, Matthew; Imrie, Helen; Kate Gatenby, Victoria; Skromna, Anna; Wheatcroft, Stephen; et al.
Abstract : Introduction: Insulin resistance is independently associated with cardiovascular events. We have previously shown that mice haploinsufficient for the insulin receptor (IRKO) exhibit hypertension, vasomotor dysfunction and impaired endothelial regeneration after denuding arterial injury, with concomitant reductions in endothelial progenitor cell (EPC) number and function. Importantly, these occur despite preserved glucocompetence. Murine models of endothelium-specific insulin resistance yield similar findings, implying that vascular insulin signalling plays a key role in maintaining functional vascular integrity. We hypothesise that selective restoration of endothelial insulin signalling can improve vascular function in the context of global insulin resistance. Methods: We have generated transgenic mice in which the Tie-2 promoter targets human insulin receptor (IR) over-expression to endothelial cells (HIRECO). These mice were crossed with IRKO to derive HIRECOxIRKO offspring, which were compared with IRKO littermates. Metabolic phenotypes were assessed using glucose- and insulin-tolerance tests, and ELISA for plasma insulin concentrations. Femoral artery injury was performed using angioplasty guide wires; vessels were explanted 4 days later to quantify endothelial regeneration using Evans Blue dye. C-kit-expressing circulating progenitor cells (CPC) were enumerated using FACS, while cultured blood-derived EPCs were counted using DiI-ac-LDL/lectin staining. Finally, aortic rings were exposed to incremental acetylcholine (ACh) and phenylephrine (PE) doses in organ bath apparatus to assess endothelium-dependent vasorelaxation and constriction respectively. Data are expressed as mean (SE) and compared using t-tests; p < 0.05 is denoted with *. Results: HIRECOxIRKO and IRKO had similar glucocompetence, insulin sensitivity, and fasting insulin concentrations [0.76 (0.14) ng/mL vs. 0.70 (0.18); p = 0.78]. Vascular regeneration was improved in HIRECOxIRKO [56.9 (4.2)% re-endothelialised vs. 46.0 (2.3)% in IRKO*]. This was not associated with improved numbers of peripheral blood CPC [212.3 (44.8) vs. 212.5 (43.9); p = 0.99], nor blood-derived EPCs in culture [0.5 (0.1)/HPF vs. 0.5 (0.2); p = 0.99]. In organ bath experiments, HIRECOxIRKO aortic rings demonstrated significantly greater ACh-induced relaxation than IRKO [Emax 99.8 (4.8)% of pre-constriction vs. 74.3 (9.3)%*] with a similar trend in PE constriction. Conclusions: Endothelial insulin sensitisation in the context of global insulin resistance rescues vasomotor function and vascular repair, despite not altering metabolic function, CPC or EPC abundance. These data imply that endothelial insulin sensitisation may be a therapeutic target to augment vascular function and repair in insulin resistant subjects.